6-Hydroxyflavanone treats anxiety and chemotherapy-induced neuropathy in Sprague–Dawley rats - Akbar, Shehla; Subhan, Fazal; Qamar, Rida; Akbar, Aroosha; Shahbaz, Naila; Aamir, Muhammad; Siddique, Nayyer; Islam, Salman Ul (Frontiers in Pharmacology, 2024)
Background: Cancer remains the fore runner in causing extensive deaths worldwide. The advent of effective chemotherapy has enormously decreased the mortality rate and increased the life expectancy of cancer patients. However, the adverse effects allied with chemotherapy contribute to the development of neurotoxicity, anxiety, and depression.The dual effect of a novel flavanone, 6-hydroxyflavanone (6-HF), was investigated in treating chemotherapy-induced neuropathy along with anxiolytic propensity.The anti-neuropathy propensity of the 6-HF was evaluated utilizing cisplatin-induced neuropathy (CIN) model, whereas its anxiolytic activity was evaluated utilizing anxiety models such as elevated plus-maze test (EPM), staircase test and open-field paradigm.Result: Cisplatin administration induced static and dynamic allodynia in the rats. Concomitant administration of 6-HF and cisplatin for four successive weeks remarkably reduced the chemotherapy-induced mechanical allodynia, evident from an elevation in the paw withdrawal threshold (PWT) and paw withdrawal latency (PWL). The anxiolytic-like activity of 6-HF in the EPM apparatus was confirmed by the increased number of entries in the open arm and time spent at the central platform, which was further confirmed by the enhanced head-dipping frequency in the same assay. A decrease in rearing behavior of the mice without suppression of the steps ascended further assured the anxiolytic-like potential of 6-HF. Additionally, the animals under investigation spent more time at the intersection of the open-field apparatus; further confirming the anxiolytic potential of 6-HF.6-HF might be considered as a potential therapeutic agent for counteracting the most common adverse effects of chemotherapy such as neurotoxicity and anxiety.